Urgensi Pengaturan Victim Impact Statement Dalam Perkara Tindak Pidana Kekerasan Seksual Berdasarkan Kepentingan Terbaik Bagi Korban - Novi Nadia; Ayu Izza Elvany (Fakultas Hukum Universitas Islam Indonesia, 2025)
Victim impact statement (VIS) in cases of sexual violence that contains information about tehe physical, psychology, economic, and social impacts. VIS is an instrument for judges to consider in determining the verdict. The Indonesian government has specific regulations regarding this, however, there is a need for the implementation of VIS for justice, certainty, and protection for victims as well as to reduce the focus on perpetrators in the justice system. This type of research is normative legal research that analyzes using existing legislative documents or regulations and focuses on positive law, utilizing conceptual approaches, legislative approaches, and comparative approaches. The explicit arrangement of Victim Impact Statements (VIS) for the legal protection of victims of sexual violence and assisting judges in understanding the impact of crimes, promoting restorative justice and the fulfillment of rights reflecting the best interests of victims as outlined in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. The importance of this arrangement is emphasized for the increasing cases, the stigma of revictimization, which is neglected in a legal system still oriented towards the perpetrators, necessitating an official regulation through a Supreme Court Circular (SEMA) so that VIS can serve as a legitimate guideline in considering legal decisions that protect victims.